Analysis of the impact of insecurity on youth unemployment in Nigeria (1990-2020) - Ibrahim Musa (Universitas Airlangga, 2023)
Youth unemployment is a very important socioeconomic problem in Nigeria, which has gone bad in recent years. Therefore, using the ordinary least square estimation technique (OLS), this research examines the impact of insecurity on youth unemployment in Nigeria from 1990 to 2020. The study focuses on the relationship between the dependent variable, unemployment (Unemp), and two independent variables, the National Terrorism Index (Ntix) and Crime Rate (Crat). The results reveal that Ntix has a positive and statistically significant effect on Unemp. Specifically, a unit increase in Ntix leads to a 0.000827 rise in unemployment. Additionally, Nigerian Crat demonstrates a significant and positive influence on Unemp, with an increase in Crat resulting in a 0.005653 increase in unemployment. Given that heightened insecurity directly contributes to unemployment, the study proposes several policy recommendations. Firstly, the government should consider reducing interest rates in commercial banks to enhance the availability of loans for small business owners, enabling them to hire more employees. Furthermore, addressing corruption in both public and private sectors, combating kidnappings, and establishing additional skill acquisition centers are crucial measures to tackle the issue of insecurity and promote employment opportunities.